2009
DOI: 10.1007/s10905-009-9190-3
|View full text |Cite
|
Sign up to set email alerts
|

Video-tracking and On-plant Tests Show Cry1Ab Resistance Influences Behavior and Survival of Neonate Ostrinia nubilalis Following Exposure to Bt Maize

Abstract: To examine how resistance to Bacillus thuringiensis (Bt) toxins influences movement and survival of European corn borer (Ostrinia nubilalis [Hübner]) neonates, the responses of Cry1Ab-resistant , -susceptible, and hybrid (F1) larvae were examined using two different techniques. First, using an automated videotracking system, aspects of O. nubilalis movement were quantified in the presence of artificial diet incorporating 50% non-Bt or insect-resistant Cry1Ab maize tissue. Second, O. nubilalis dispersal and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 23 publications
1
20
1
1
Order By: Relevance
“…They studied movement and survival of three genotypes of larvae on one kind of transgenic corn. Prasifka et al (2009Prasifka et al ( , 2010 studied two genotypes of larvae under different conditions by using another transgenic insecticidal corn trait. Prasifka et al (2010) found that Cry1Ab resistant larvae had a higher probability of leaving a Bt corn plant for an adjacent non-Bt plant than did susceptible larvae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They studied movement and survival of three genotypes of larvae on one kind of transgenic corn. Prasifka et al (2009Prasifka et al ( , 2010 studied two genotypes of larvae under different conditions by using another transgenic insecticidal corn trait. Prasifka et al (2010) found that Cry1Ab resistant larvae had a higher probability of leaving a Bt corn plant for an adjacent non-Bt plant than did susceptible larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Prasifka et al (2009Prasifka et al ( , 2010 studied two genotypes of larvae under different conditions by using another transgenic insecticidal corn trait. Prasifka et al (2010) found that Cry1Ab resistant larvae had a higher probability of leaving a Bt corn plant for an adjacent non-Bt plant than did susceptible larvae. Yet S. E. Moser et al (unpublished data) observed that susceptible larvae disperse from Cry1 Fexpressing corn more than Cry1 F-resistant larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Pollen expression data compared with other studies are few and the mortality of the control is unacceptably high. In a further study, Xing et al (2008) observed that Bt-proteins in maize pollen were not detectable after 15 or 18 days, depending on the event Changes in feeding behaviour of lepidopteran larvae Scientific publications report examples of feeding inhibition, repellent effects and changes in feeding behaviour, particularly for Cry1F protein (Prasifka et al, 2007(Prasifka et al, , 2009Goldstein et al, 2010;Gaspers et al, 2011). In contrast, Halcomb et al (2000) observed no repellent effect on two lepidopteran species feeding on GM cotton expressing Only a limited number of lepidopteran species might be at risk.…”
Section: Degradation Of the Btprotein In Pollenmentioning
confidence: 99%
“…노린재류의 집합페로몬은 먹이가 있는 경우 분비함 으로 (Morishima et al, 2005;Huh and Park, 2006), 집 합페로몬과 콩 종실을 조합하면 노린재류의 유인효과가 증 진한다고 하였다 (Huh and Park, 2006;Yasuda et al, 2007). 근년에 Video Tracking System(VTS)를 이용하여 곤충의 행동양상을 보다 정밀하게 관찰하는 연구가 활발하 게 이루어지고 있다 (Noldus et al, 2002;Prasifka et al, 2010) 에 차이가 있다 (Oh, 2008). …”
Section: 서 론 국내에서 식식성 노린재류에 의한 두과 및 과수작물 등 의 수량감소 및 품질저하가 크게 문제되기 unclassified